The moment generating function of a reflected Brownian motion with drift - Fredrik Armerin (Results in Applied Mathematics, 2025)
We derive an explicit formula for the moment generating function of a Brownian motion with drift reflected from above in one barrier. Some other properties of this stochastic process are also reported.